2014
DOI: 10.1177/2325957414530472
|View full text |Cite
|
Sign up to set email alerts
|

Normal CD4 Count Range among Healthy Nigerian Population in Ilorin

Abstract: We therefore advocate the use of CD4 count range derived in this study is lower than that of the national reference values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…Additionally, urban vaccine study participants demonstrated higher granulocyte counts. Here we show that, consistent with other studies in Africa [ 6 , 21 , 23 , 33 ], and elsewhere [ 21 , 34 ] populations in different geographic locations may have statistically significant differences in lymphocyte and other hematological parameters. The reason for this variation across Ugandan populations remains unclear.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, urban vaccine study participants demonstrated higher granulocyte counts. Here we show that, consistent with other studies in Africa [ 6 , 21 , 23 , 33 ], and elsewhere [ 21 , 34 ] populations in different geographic locations may have statistically significant differences in lymphocyte and other hematological parameters. The reason for this variation across Ugandan populations remains unclear.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with other studies done in Uganda and elsewhere, for T cell subsets [ 4 6 , 9 , 18 21 ]. Also, immunological differences between male and female children have previously been observed, albeit not consistently [ 20 23 ]. The underlying basis for this sex difference has not been elucidated, however variance in the normal ranges of lymphocyte subsets may contribute to differential immune responses to infection, vaccination, or treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, absolute count CD4 T cell counts were higher in females compared to males which is similar to findings from studies in other African and Asian countries [6,8,13,14,34], which has been associated with hormonal differences [61]. The median CD4 count in this cohort is comparable to those reported from the Central African Republic [12] and Malawi [56] but is higher than median values from Tanzania [10], Nigeria [62], Uganda [6], and Ethiopia [11].…”
Section: Plos Onesupporting
confidence: 87%
“…Note that in our study, majority of the patients (81%) were currently on ART and are being monitored regularly by ART clinicians. Additionally, females represents a higher percentage of our study participants and HIV infected female individuals have been reported to have significantly higher CD4 count than their male counterparts [49]. Additionally, women generally showed consistently improved immunological response to ART treatment than men [49].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, females represents a higher percentage of our study participants and HIV infected female individuals have been reported to have significantly higher CD4 count than their male counterparts [49]. Additionally, women generally showed consistently improved immunological response to ART treatment than men [49]. Women also do present to hospital earlier than men thereby promoting better uptake of HIV treatment among women which further contribute to improve immunologic outcomes than men [50].…”
Section: Discussionmentioning
confidence: 99%